Conditores Urbis Romae, Liwiusz i rzymskie numizmaty = Conditores Urbis Romae, Livius and ancient Roman coins - Kluczek, Agata Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In a description of a monument erected ad ficum Ruminalem by Ogulnii in 296 BC, T. Livius used the term conditores Urbis in reference to children who appear with the she-wolf. This is one of very rare examples of the use of this term by the historian in the Ab urbe condita. Such reference to the protagonists of the monument of the Ogulnii manifests an analogy in the content of the dedication of the monument (Marti invicto patri et aeternae urbis suae conditoribus), of which only the base with an inscription which dates back to the reign of emperor Maxentius (306-312) is preserved.
Keywords: Romulus; założyciele Rzymu; Titus Livius (59 p.n.e.- 17 n.e.); Maksencjusz (cesarz rzymski; 280-312); monument Ogulniuszów; moneta rzymska; ikonografia monetarna; founders of the city of Rome; monument of the Ogulnii; Roman coin; monetary iconography